A Swollenin From Talaromyces leycettanus JCM12802 Enhances Cellulase Hydrolysis Toward Various Substrates - Zhang, Honghai; Wang, Yuan; Brunecky, Roman; Yao, Bin; Xie, Xiangming; Zheng, Fei; Luo, Huiying (Frontiers in Microbiology, 2021)
Swollenins exist within some fungal species and are candidate accessory proteins for the biodegradation of cellulosic substrates. Here, we describe the identification of a swollenin gene, Tlswo, in Talaromyces leycettanus JCM12802. Tlswo was successfully expressed in both Trichoderma reesei and Pichia pastoris. Assay results indicate that TlSWO is capable of releasing reducing sugars from lichenan, barley β-glucan, carboxymethyl cellulose sodium (CMC-Na) and laminarin. The specific activity of TlSWO towards lichenan, barley β-glucan, carboxymethyl cellulose sodium (CMC-Na) and laminarin is 9.0 ± 0.100, 8.9 ± 0.100, 2.3 ± 0.002 and 0.79 ± 0.002 U/mg, respectively. Additionally, TlSWO had disruptive activity on Avicel and a synergistic effect with cellobiohydrolases, increasing the activity on pretreated corn stover by up to 72.2%. The functional diversity of TlSWO broadens its applicability in experimental settings, and indicating that it may be a promising candidate for future industrial applications.